Concentration, Barriers to Entry and Rates of Return - George, K. D. (The Review of Economics and Statistics, 1968)
the value of exports. The analysis is based on cross-sectional value and quantity series, and it is conceivable that the quantity data, from which our unit value series are constructed, contain a fair margin of errors. The reliability of unit values with respect to the aggregation problem is examined, and measurement errors in the quantity series may have biased our estimates of elasticities towards minus one. Since it is often the case that the estimation of price elasticities in international trade has to rely on unit value series, we maintain that bias due to inaccurate quantity data should be taken seriously.